2013
DOI: 10.1007/s00268-013-2314-0
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Surgery in the Developing World: Workforce and Operative Volumes in Ghana Compared to Those in the United States

Abstract: Annual case volume at a referral hospital in an LMIC is equivalent to that of a level I trauma center in an industrialized country. Total case volume is similar, but the LMIC institution manages a disproportionately large number of trauma cases, severe fractures, and infections. There is a large burden of orthopedic disease in the developing nation, and there are too few providers and training programs to address these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 59 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Educational Programs: Programs reported on efforts to develop locally relevant curricula by reviewing case data from local specialists. [24][25][26][27][28] Programs also reflected on the lack of relevant standards to guide education, and the need to ensure locally relevant curricula especially when international partners were involved. 26,28,[29][30][31][32][33][34][35][36][37][38] Suggestions included having partners co-develop curricula to ensure local relevance.…”
Section: Thematic Analysis Of Lessons Learned From Specific Pgme Progmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational Programs: Programs reported on efforts to develop locally relevant curricula by reviewing case data from local specialists. [24][25][26][27][28] Programs also reflected on the lack of relevant standards to guide education, and the need to ensure locally relevant curricula especially when international partners were involved. 26,28,[29][30][31][32][33][34][35][36][37][38] Suggestions included having partners co-develop curricula to ensure local relevance.…”
Section: Thematic Analysis Of Lessons Learned From Specific Pgme Progmentioning
confidence: 99%
“…8,36,76,96,101,103,104,111,[115][116][117][118][119] Health Care Workforce Priorities and Retention of Graduates in Region Programs described the need for targeted research on the burden of non-communicable diseases to advocate for the training of specialists and to counter the previous predominant focus on infectious diseases. 24,40,63,71,98,118,120,121 Publications also reported on the benefits of simultaneously establishing training programs in fields that are complementary such as surgery and anesthesia. 29,71,98,110,122 Programs reported that retention of graduates was influenced by location of training as well as career prospects and employment opportunities after graduation.…”
Section: Thematic Analysis Of Lessons Learned From Specific Pgme Progmentioning
confidence: 99%
“…This entails an increase in the average life expectancy and a consequent exposure of the population to the so-called man-made diseases [2][3][4] . Despite this growing burden, orthopaedic care in the developing world remains scarce when compared with developed countries, with only one in three people provided for [5] . This disparity in demand and supply of orthopaedic care has implications for orthopaedic training across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…12 To illustrate this point, 95% of all operations at a hospital in Ghana were trauma-related procedures compared with 65% at a US hospital in San Francisco. 13 Orthopedic disease is an underrecognized, underfunded, and shockingly significant contribution to the burden of disease in LMICs.…”
mentioning
confidence: 99%
“…9 To illustrate this shortage, there are 24 orthopedic surgeons in Ghana and 23,956 in the United States. 13 Ghana has a population roughly 11x smaller than that of the US, yet the number of orthopedic surgeons in Ghana is almost 1000x smaller. Other studies have documented similar issues with access to orthopedic care in LMICs.…”
mentioning
confidence: 99%